Modeling of vapor-to-melt ratio in laser cutting aluminum alloy sheet. Issue 1 (2nd January 2016) - Luo, Yonghao; Wang, Xuyue; Meng, Qingxuan; Xu, Wenji; Kang, Renke; Guo, Dongming
ABSTRACT: To study the regular pattern of vapor-to-melt ratio in laser cutting sheet metal, a physical model of vapor-to-melt ratio is developed to demonstrate the material remove forms of vaporization-melt in cutting area and the state of energy and mass flow in the molten layer. Variation of vapor-to-melt ratio with laser power and cutting velocity is obtained by laser cutting of 6063 aluminum alloy sheet. The 0.5-mm sheet thickness is carried out on a JK701H Nd:YAG pulse laser cutting system by simulating under the regression correction of cut radius. Observation on the cut samples with different parameters (65 W, 85 W, 105 W varied with laser power increasing, and 2.2 mm/s, 2.0 mm/s, 1.8 mm/s with decreasing of beam cutting speed) and the calculations show that vapor-to-melt ratio increases (0.595–1.995, 0.672–2.631, 0.787–4.171) with laser power (65 W–110 W) and decreases with cutting velocity (1.8 mm/s–2.4 mm/s). At the same time, the laser cutting quality increases with vapor-to-melt ratio and the decrease with thickness of residual molten layer. The results show good agreement between vapor-to-melt ratio model and experiments. The analysis verifies that this model is feasible and it makes contribution to laser precision cutting.